Complications Following Brachial Arterial Catheterization in the Surgical Intensive Care Unit. Issue 10 (26th October 2020) - Schellenberg, Morgan; Hawley, Lauren; Biswas, Subarna; Clark, Damon H.; Cobb, J. Perren
Clinically, complication rates of brachial arterial catheterization appear to far exceed those of the radial or common femoral arteries. The study objective was to define the complication rate after brachial arterial line insertion. All patients undergoing arterial line placement to the brachial artery in the surgical intensive care units (SICUs) at our institution were retrospectively identified and included in the study (January 2016-December 2018). Demographics, complications (distal ischemia, thrombosis/dissection, brachial sheath hematoma, catheter-related sepsis, and inadvertent dislodgement), and outcomes were collected and analyzed. Over the study period, 53 patients underwent brachial arterial catheterization. Common admitting services were cardiothoracic surgery (n = 31, 58%), transplant surgery (n = 7, 13%), and neurosurgery (n = 4, 7%). The mean age was 55 ± 17 58 (24-84) years, and 58% (n = 31) were male. The hospital length of stay (LOS) was 37 ± 35 23 (1-132) days, and ICU LOS was 30 ± 27 20 (1-127) days. Mortality was 57% (n = 30). Complications of brachial arterial line placement occurred in 21 patients (40%). In summary, brachial arterial catheters were associated with high mortality and prolonged ICU length of stay. This likely reflects the critically ill nature of patients in whom conventional-site arterial line placement is not possible. Complications following brachial arterial catheterization were unacceptably high. On this basis, we recommend that the brachial artery be avoided whenever possible for arterial line placement in the SICU.